Parental actions that correlate with preschoolers requesting larger portions of food when away from home - Wansink, Brian; Wansink, Audrey (International Journal Of Community Medicine And Public Health, 2022)
Background: How does a parent’s action at home sabotage the way their child eats when they are not at home? This two-part study explored which parental behaviors at home were most correlated with 75 preschooler’s requests for larger servings of snacks when away from home and away from parental scrutiny. Methods: Primary meal providers of three- to five-year old children completed surveys describing how they served food and snacks at home (such as whether they were always available in any amount a child wanted) and a wide range of questions about snacking habits of their children. Two weeks later, their children were met (without their parents present) and asked to indicate how much Froot Loops (a popular pre-sweetened cereal) they wanted for their morning snack. Correlations between how much they served and household snacking behaviors were then explored. Results: Boys who were often required to clean their plates at home requested more cereal during snack time when away from home (p<0.05), and daughters who were able to snack at home whenever at home whether they wanted also requested more (p<0.05). Girls who were frequently given fruit as a snack at home requested less presweetened cereal when away from home (p<0.01). Conclusions: Parent actions in the home might have an unexpected impact on how much of less healthy foods children request when they away from such parental oversight. Care must be taken so a parent does not win a food battle at home just to lose any away-from-home food war.